2014
DOI: 10.1111/papr.12206
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Fentanyl and Flurbiprofen Axetil on Serum VEGF‐C, TNF‐α, and IL‐1ß Concentrations in Women Undergoing Surgery for Breast Cancer

Abstract: In patients undergoing a mastectomy, postoperative analgesia with flurbiprofen axetil, combined with fentanyl, were associated with decreases in serum concentrations of VEGF-C, TNF-α, and IL-1ß compared with patients receiving doses of only fentanyl.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 34 publications
0
28
0
Order By: Relevance
“…In this study, satisfactory analgesia was achieved in both groups but the sufentanil consumption of PCA in the SF group was not reduced than that in the S group. It was reported that flurbiprofen axetil combined with smaller dosage of fentanyl significantly enhanced analgesia effect and reduced side effects of vomiting (Wen et al, ). However, in other studies, postoperative administration of flurbiprofen axetil, 100 mg/day, did not reduce the opioids consumption or improve analgesia effects (Liu, Chai, & Chen, ; Nonaka, Hara, Miyamoto, Sugita, & Yamamoto, ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, satisfactory analgesia was achieved in both groups but the sufentanil consumption of PCA in the SF group was not reduced than that in the S group. It was reported that flurbiprofen axetil combined with smaller dosage of fentanyl significantly enhanced analgesia effect and reduced side effects of vomiting (Wen et al, ). However, in other studies, postoperative administration of flurbiprofen axetil, 100 mg/day, did not reduce the opioids consumption or improve analgesia effects (Liu, Chai, & Chen, ; Nonaka, Hara, Miyamoto, Sugita, & Yamamoto, ).…”
Section: Discussionmentioning
confidence: 99%
“…11 Wen et al showed that flurbiprofen decreased VEGF-C, TNF-α, and IL-1β serum levels compared to fentanyl in patients undergoing mastectomy. 28 Narahara et al showed better cytotoxic immune function in patients receiving flurbiprofen compared to fentanyl. 29 In the present study, the slight immune suppression observed at the end of surgery in all three groups was not affected by flurbiprofen preemptive analgesia.…”
Section: Discussionmentioning
confidence: 99%
“…Shen et al showed that flurbiprofen combined with morphine could improve immune suppression in T and NK cells in cancer patients . Wen et al showed that flurbiprofen decreased VEGF‐C, TNF‐α, and IL‐1β serum levels compared to fentanyl in patients undergoing mastectomy . Narahara et al showed better cytotoxic immune function in patients receiving flurbiprofen compared to fentanyl .…”
Section: Discussionmentioning
confidence: 99%
“…While the patients of breast cancer were waiting for surgery treatment, the states of circadian disruption [49], improved serum levels of oxidative damage [50], inflammatory biomarkers and angiogenic factors [51] would make the tumor progress. These researches focused either on oxidative stress or on inflammatory states.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that elevated inflammatory mediators including vascular endothelial growth factor-C (VEGF-C), tumor necrosis factor-α (TNF-α), and interleukin-1ß (IL-1ß) are associated with increased rates of breast cancer recurrence and metastasis of following surgery [14][15][16].Inflammatory biomarkers and scores are potentially important prognostic factors in breast cancer during the perioperative period.…”
Section: Introductionmentioning
confidence: 99%